Fortunata's Vestige: An Alchemic Clue to the Ancient Cosmos (Dmitry Merezhkovsky's "Julien the Apostate") - Lyutskanov, Yordan (Amaltea. Revista de Mitocrítica, 2011)
This work inspects important passages of the first Russian modernist novel. It inquires the novel’s discourse, which hesitates between naturalism and symbolism and, in particular, between representing the nineteenth-century scientific image of the world, and representing –or rather, resurrecting – an ancient image of it – the cosmos of four elements. It focuses on a symbolist (in a sense close to Baudelaire and the “correspondences”) recreation of an ancient (pagan and Greco-Roman) topos (in a sense close to that of E. R. Curtius’s): that of Fortuna and of the reiterated wisdom that Fortuna raises people’s lives up and crushes them down. Further on, it reviews the use of the topos mentioned from the point of view of the philosophy of history and of the history of art. Starting with certain passing observations, Merezhkovsky’s views are linked to the history of Orientalism (in a Saidian sense). Then, a step is taken towards putting the implicit historiosophic and aesthetic dispositions of the novel into its context, the 1890s, by paying attention to Vladimir Solovyov’s and Ernest Renan’s intertextual presence in the novel, and to academism and impressionism. A number of passages where Merezhkovsky’s novel revisits classical literature (Plutarch, Strabo, Xenophon) have also been analysed. Thus, this article demonstrates the classicising symbolism of Merezhkovsky’s early fiction.